Effects of nicotinamide riboside in ovo feeding on high-yield broiler performance, meat quality, and myopathy incidence - Maynard, Clay J.; Gonzalez, John M.; Haginouchi, Taketo; Ellis, Olivia G.; Jackson, Ashunti R.; Owens, Casey M. (Frontiers in Physiology, 2024)
The objective of this study was to examine the effects of in ovo nicotinamide riboside (NR) feeding on high-yield broiler growth and meat quality. Fertilized Cobb 700 by-product eggs (N = 3,240) were randomly assigned to one of four in ovo treatments and injected with 0 (0NR), 250 (250NR), 500 (500NR), or 1,000 (1,000NR) mM NR at incubation-day 10. Chicks were hatched, vent sexed, and randomly placed 18 per pen in one of 32 floor pens. On day 48, birds were processed and deboned. There were dose effects for all part weights (P < 0.05). Pectoralis major weight of 250, 500, and 1,000NR carcasses were heavier than 0NR (P < 0.03) but did not differ from remaining NR doses (P > 0.26). Pectoralis minor weight of 250NR carcasses was greater (P < 0.01) than 0NR and did not differ from other NR tenders (P > 0.21). Pectoralis minor weight of 500 and 1,000NR carcasses was greater than 0NR (P < 0.09), but did not differ (P = 0.82) from each other. There were no dose effects for all Pectoralis major and minor myopathy scores and incidence except incidence of tenders scoring "0" and "1" for woody-like tender. Percentage of NR1,000 tenders scoring 0 and 1 for woody-like tender were less than and greater than all other treatments, respectively (P < 0.05). There were no differences among remaining NR doses and NR0 tenders (P > 0.10). There were dose effects for muscle fiber number (P = 0.03). There tended to be more muscle fibers within 250 and 1,000NR muscles compared to 0NR (P < 0.09). Pectoralis major muscle from 500NR did not differ in muscle fiber number compared to 250 and 1,000NR (P > 0.18), but had more (P < 0.01) fibers than 0NR muscle. There tended to be more fibers in 250 and 1,000NR muscles compared to 0NR muscle (P < 0.09). Nicotinamide riboside in ovo feeding caused birds to produce heavier parts; however, myopathy scores and incidence were minimally affected which may have been due greater muscle fiber number.